The Effect of Farmer Knowledge, Farmer Attitudes, and Farmer Skills on Farmer Decisions in Bakalan Village, East Java Province, Indonesia - Wasono, Didik Mulyo; Muhaimin, A. Wahib; Isaskar, Riyanti (Agro Bali : Agricultural Journal, 2024)
The Bakalan Village Government and the Bojonegoro Regency Agriculture Office in 2023, organized the Integrated Pest Management Field School to educate farmers about environmentally friendly agriculture and more sustainable pest control methods, to increase crop yields and farmer welfare. This study was conducted to analyze the influence of farmer behaviour in SLPHT activities on farmer decisions. Respondents were selected using the Slovin formula calculated by population. The study population was 80 farmers from 4 farmer groups in Bakalan Village. Thus, a research sample of 45 farmers was obtained. Data analysis was conducted using multiple linear regression methods with data processing tools using SPSS. The results explained that farmer knowledge, farmer attitudes and farmer skills influenced farmers' decisions in SLPHT activities. Farmer knowledge is the highest factor or influence in influencing farmers' decisions on SLPHT activities. This research is useful for farmers participating in SLPHT because farmers can continue to apply the farming methods obtained in SLPHT activities and provide information to other farmers, and further guidance needs to be held to determine the sustainability and application of farming methods obtained from SLPHT activities.